Emerging Issues and Opportunities in Disaster Response Supply Chain Management - Dash, Shisira Ranjan; Mishra, Uma Sankar; Mishra, Pallavi (International Journal of Supply Chain Management, 2013)
The world is facing an increasing frequency and intensity of disasters both natural and man-made that have devastating impact on life, livelihood and economy of the affected communities. In the context it is very important to plan for disaster response activities and preparedness to minimize the economic and human loss. In a post disaster situation various aid organizations and government agencies start supplying food, water, clothing, medicines and other emergency relief materials efficiently and quickly to maximize survival rate and continue normalcy. However, managing disaster response supply chain is not that straight forward. In most disasters, information is scarce (between the supplier and end users) and coordination rarely exists (Long & Wood, 1995) which creates disruption in flow of supply chain. Hence disaster response supply chain operates in a level of high uncertainty and is very different from what most supply chain managers perceive. This article describes the main characteristics of disaster response supply chain, particular issues faced by the managers and the opportunities on which the future strategy could be capitalized. It also suggests a model that captures the interaction between different components of supply chain and controls the flow of the commodities from the source through the chain to reach the end users.